Economics of Milk Production in Kumaon Region of Uttarakhand - Bardhan, D; Sharma, M L (Indian Journal of Dairy Science, 2012)
The study was carried out on 150 milk producing households in Kumaon region of Uttarakhand to compare the costs and returns from milk production at farm household level across member and non-members of Milk Producers’ Cooperative Societies. The findings of the analysis revealed that in the plains, relatively higher net maintenance cost per standard animal unit (SAU) was incurred by member group as compared to the non-member group. In contrast, in the hills, the average net maintenance cost per SAU was higher for non-member group than that of member group. Average net maintenance cost tended to decline with increase in herd size across groups. The proportion of fixed cost in gross cost was comparatively lesser in hills than in plains, indicating towards relatively lower level of investment made by farmers in dairying in the hills than in plains. Computation of different income measures revealed that both in the plains and hills, dairying is more profitable for the non-member households as compared to their member counterparts. The income measures also indicated that dairying becomes more or less profitable only when family labour charges are ignored.